PENYULUHAN TENTANG COVID-19 DAN TATA LAKSANANYA DI KECAMATAN MANGGALA KOTA MAKASSAR - Anita Anita; Darmawaty Rauf; Suardi Suardi (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2021)
Coronaviruses are a group of viruses that cause respiratory disorders caused by the Sars-CoV-2 virus that has never been previously identified in humans. COVID-19 can be transmitted through coughing/sneezing droplets from human to human. Therefore, standard recommendations as a preventive measure for COVID-19 transmission must be carried out as early as possible, which can be carried out by providing health education to the community through community service activities at Al-Hidayah Perumnas Antang Makassar City. Knowledge of how to avoid COVID-19 disease and health maintenance will automatically increase public knowledge. The public's knowledge and understanding of the corona virus can be interpreted as the result of knowing the public about how to prevent, treat and treat complications. The purpose of this counseling is to increase the understanding of the congregation of Mesjdi Al-Hidayah Perumnas Antang Makassar City regarding COVID-19 and its management. The method used in this counseling is a lecture and discussion method involving interaction between participants and the extension team. From this counseling activity, it is hoped that there will be an increase in the understanding of counseling participants about COVID-19 and its management. From this community service activity, it can be concluded that the extension participants have increased understanding of COVID-19 and its management starting with prevention, treatment and complications